THE EFFECT OF MANGANESE SOURCE ON NUTRITIVE AND BIOPRODUCTIVE INDICES AT BROILER CHICKENS - C. JULEAN; D. DRINCEANU; I. LUCA; LAVINIA ȘTEF; ELIZA SIMIZ; C. MEDREA; D. FOTA (Scientific Papers Animal Science and Biotechnologies, 2023)
In this experiment we studied the effect of chelated manganese from phosphatic glass soluble in acids, phosphatic glass semi soluble in water and phosphatic glass soluble in water and inorganic salts (Mn SO4) on nutritive and bioproductive indices at broiler chickens. Mineral premix, made on calcium carbonate differentiate by manganese supplementation source, and was assured a level of 30.00 mg active Mn. The experiment was carried out on 120 broiler chickens divided in four experimental groups (CL-V1, EL-V2, EL-V3 and EL-V4), respectively 30 chickens per group. The hybrid used was Ross 308. The manganase assurance from phosphatic glass soluble in acids, phosphatic glass semi soluble in water and phosphatic glass soluble in water determine a decrease of manganese content in the poultry litter comparative with the manganese assurance from manganese sulfate. The manganese assurance from phosphatic glass soluble in water determines the increasing of the bioproductive indices with 5% comparative with the manganese assurance from manganese sulfate.